First isolation of Brevibacterium sp. pigments in the rind of an industrial red‐smear‐ripened soft cheese. (27th January 2015) - Galaup, Patrick; Sutthiwong, Nuthathai; Leclercq‐Perlat, Marie‐Noëlle; Valla, Alain; Caro, Yanis; Fouillaud, Mireille; Guérard, Fabienne; Dufossé, Laurent
Abstract : The smear‐ripened soft cheeses are characterised by a surface orange‐red‐brown colour, which has a microbial origin. For a long time, this colouration was mainly imputed to Brevibacterium linens . However, the latest published works, based on molecular biology, have shown a minor role for this bacterium. This study shows the results obtained with an industrial cheese named Vieux‐Pané, which is characterised by the presence of carotenoids from Brevibacterium linens group at its surface. This demonstrates that, under certain conditions, the Brevibacterium linens group ( Brevibacterium linens and Brevibacterium aurantiacum sp. nov.) is able to produce pigments and to colour cheeses effectively.